Football shoes - Are they a risk factor for injuries? - Gehring, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The shoe of the football player is specifically discussed to be an external risk factor of injuries as the athlete wears a cleated football shoe that penetrates an uneven turf. Based on a systematic literature review this talk summarizes the current knowledge about the shoeground interaction in football and its relevance with respect to injuries. This talk will show how different surface conditions like dry vs. wet grass or different kinds of natural grass influence injury occurrences. Moreover, we will answer the question if newest generations of artificial turf increase the injury risk compared to natural grass (Williams et al. 2011). We will then describe the concept of traction, which is closely related to this question and which describes the resistance of the shoe against sliding and rotational motion on the ground. Literature reveals that there is a clear effect of traction properties on the athlete`s performance (e.g. Sterzing et al. 2010) but as well on the injury risk. We will demonstrate that it is important to differentiate the traction properties of a shoe carefully; as for instance a higher rotational traction is associated with an increased injury risk but a higher translational traction with a reduced injury rate (Wannop et al. 2013). Finally, we will make conclusions about the `ideal` shoe in order to prevent football injuries.